Strategi misi Kristen memisahkan Islam dan Jawa - Susiyanto, 1982- (Jakarta : Cakra Lintas Media : Distributor tunggal, Buku Kita, 2010)
On Christian missions in separating Islam from Javanese culture
Includes bibliographical references (p. [253]-267)
Keywords: Missions -- Indonesia -- Java; Christianity and other religions -- Indonesia -- Java; Islam -- Relations -- Christianity; Java (Indonesia) -- Civilization